Pengaruh Jumlah Komite Audit, Ukuran Perusahaan dan Audit Report Lag terhadap Kualitas Audit (Studi Empiris Perusahaan Industri Dasar dan Kimia yang Terdaftar di BEI 2016-2020) - Abigail Dwi Pangestu Setiadi; Valentine Siagian (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
Audit quality is very important for a company, therefore this study aims to see whether company size, number of audit committees, and audit report lag can affect audit quality. The data used in this study is secondary data which will be analyzed using SPSS. Significant results were obtained from the size of the company and the number of audit committees, while the audit report lag in this study could not affect audit quality.